THE APPLICATION OF CONSCIOUSNESS RAISING METHOD IN TEACHING WRITING TO THE TENTH GRADE STUDENTS OF STATE SENIOR HIGH SCHOOL 8 OF PALEMBANG - Noviati Noviati (HOLISTICS, 2020)
Abstract: This study focused on the Application of Consciousness Raising Method in Teaching Writing to theTenth Grade Students of State Senior High School 8 of Palembang. In this study, the materials were limited torecount essays in the theme of Personal experience that consist of 3 simple paragraphs to the Tenth GradeStudents of State Senior High School 8 of Palembang. The result of the test shows that the Application ofConsciousness Raising Method in Teaching Writing to the Tenth Grade Students of State Senior High School 8of Palembang, it could help the students in making their writing recount essays better. Based on the result of thetest, the students who were taught through Consciousness Raising Method got higher scores than those whowere not. In the experimental group, the highest posttest score was 85, the lowest posttest score was 61, and theaverage was 71.30. While 79 was the highest score in the control group, the lowest posttest score was 55, andthe average was 65.53. On the other hand, the result of t obtained was 3.783. Meanwhile its critical value at 0.05significance level for one tailed test with 58 (df) was 1.671. Since the t obtained was higher than t table, Ho wasrejected and Ha was accepted. In conclusion, the Application of Consciousness Raising Method in TeachingWriting to the Tenth Grade Students of State Senior High School 8 of Palembang was effective.